Pelatihan Pembuatan Selai Mangga Sebagai Produk Olahan Tabulampot di Masyarakat Dusun Sendowo Yogyakarta - Elly Syafriani; Valentina Dwi Suci Handayani; Budiastuti Kurniasih; Siti Nurul Rofiqo Irwan; Sri Muhartini (Jurnal SOLMA, 2022)
Background: The development of tabulampot cultivation for residents of Sendowo Hamlet Yogyakarta has been carried out since 2020 with the aim of improving the function of narrow spaces and improving various nutrients in the family. Continuing the tabulampot cultivation assistance activities, the Department of Agricultural Cultivation, Faculty of Agriculture UGM in 2021, carried out a community service program in the form of propagation, maintenance, and processing of tabulampot cultivation products in Sendowo Hamlet. The processing of tabulampot cultivation results aims to provide art/skills in processing various tabulampot cultivation products. Method: With low production price, easy manufacturing method, and long-lasting results, then making mango jam is the right choice of training ideas for the people of Sendowo Hamlet. The number of trainees consists of 10 people. This activity is carried out by community education methods in the form of training and counseling. Result: The Service activity received a positive response from the people of Sendowo Hamlet. Conclusion: This activity has educated and increased the interest of the people of Sendowo Hamlet in producing mangoes harvested from tabulampot into processed products in the form of mango jam.